الانحراف الفكري مظاهره وأسبابه وعلاجه - د . علي أبو الفتح حسين حمزة (White Nile Journal for Studies and Research, 2019)
Deviation in the sense of language is meant to tend and turn away from the thing. and it is often called out from the serious and noble values, and takes the deviation of several images related to behavior and work and perception, and the deviation in thought one of those images, and meant to get out of moderation and moderation in the understanding of religious matters and applications, And thought is considered the most important characteristic of man from other creatures; but the failure to adjust the controls of science and religious guidance led to the aggravation of the phenomenon of deviation and the number of supporters and opponents of it, whether they know or do not know, and the consequences of this deviation of great effects distort religion, The Worlds Light The aim of this research was to identify the danger of intellectual deviation on individuals, groups and countries and to clarify the consequences of this disease. And the discovery of its means and manifestations, and the search for integrated solutions contribute to address this phenomenon or reduce it, and the problem of this research to identify the intellectual deviation and disclosure of manifestations, methods and effects; What are the effective methods in treatment? The researcher went through that analytical inductive method, and the researcher reached through his research that Islam is the religion of the middle and justice is far from deviation and tendency to falsehood, but it is the most religions of the deviations of intellectual emerging, and found from the research also that ignorance of religion and the symptoms of the book and the year and jealousy and enthusiasm of The greatest reasons that led to deviation in thought, which resulted in devastating effects and great risks corrupted the doctrine and questioned the religion and distorted image, and the researcher believes that adherence to the book and the year in the manner of the predecessor of the nation and the dissemination of forensic science evidence, and immunization of young people and attention to delinquents, The scholars recommend that preachers, preachers, educators and govemors should carry out their responsibilities and duties towards those under their jurisdiction.